A rapid and easy method for the purification of the Neurospora crassa NADP-specific glutamate dehydrogenase - J. Aguirre; W. Hansberg (Fungal Genetics Reports, 1988)
In order to study an oxidative modification of the Neurospora crassa NADP-specific glutamate dehydrogenase (GDH[NADP]) during aerial growth, we were compelled to purify this enzyme.